Professor Antoni Śliwiński - Jubilee - LINDE, Bogumił; MARKIEWICZ, Anna (Archives of Acoustics, 1995)
The Scientific Symposium was held on 15-th of February 1994 at Gdańsk University on the occasion of 65-th birthday of Professor Antoni Śliwiński. The Symposium was organized by the Institute of Experimental Physics (University of Gdańsk) and the Gdańsk Sections of the Polish Acoustical Society and Polish Physical Society.